Економічний розвиток Луцька в міжвоєнний період (1919-1939 рр.) - Шваб, Анатолій; Shvab, Anatolii; Малеончук, Галина; Maleonchuk, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено соціально-економічні перетворення міжвоєнного Луцька. На основі нових архівних матеріалів охарактеризовано стан розвитку промисловості, торгівлі, фінансових установ, забудови міста, соціальні перетворення та характер зайнятості його мешканців. Звернено увагу на перебіг світової економічної кризи 1929–1933 рр. у Луцьку.

The article highlights the socio-economical transformation of the interwar Lutsk. Based on new archival materials described state of the industry, trade, financial institutions, city building (improvement of streets and squares, reclamation, creation rail and road connections, conduit and sewer construction), social change and the character of employment of its residents. The authors draw attention to the progress of the global economic crisis of 1929–1933 in Lutsk, analyzing the changes in agriculture and industry, accompanied by strikes and the spread of unemployment. Submitted by periods of economic development of Lutsk in the interwar period, taking into account the political and economic situation of the Second Polish Republic, which included the city in the study period.
Economic Development of Lutsk in the Interwar Period (1919–1939 Years)
Keywords: Луцьк; економіка; підприємство; ремесло; зайнятість населення; розбудова міста; Lutck; economy; enterprise; profession; employment; development of the city